2019
DOI: 10.1002/jper.18-0604
|View full text |Cite
|
Sign up to set email alerts
|

Severe periodontitis may influence cementum and dental pulp through inflammation, oxidative stress, and apoptosis

Abstract: Background The relationship between chronic periodontitis and pulpal/cemental changes is seldom reported. This study aimed to report on the microstructural changes of cementum and histopathological features of the dental pulp in teeth with severe chronic periodontitis. Methods Eighty molar teeth with severe chronic periodontitis and 50 extracted third molars (as normal controls) were collected. The microstructure of cementum was evaluated by scanning electron microscopy, and the pulp was stained with hematoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Some of the major issues associated with PT were the tissue hypoxia, oxidative stress and relative vasospasm which in turn, determines increased coagulation and endothelial injury, damage of vascular endothelial cells, and finally periodontal tissue destruction [ 44 ]. Consequently, some evidence has been suggested that periodontal infection mediated by some pathogens such as A. actinomycetemcomitans may accelerate PT and endothelial damage and inflammatory response orchestrated through oxidative stress pathways [ 45 , 46 ], especially in obese patients [ 47 ]. In this respect, some evidence has shown that the tissue damage associated with PT was due to oxidative stress and, therefore, associated with high levels of nitric oxide (NO) and hs-CRP [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the major issues associated with PT were the tissue hypoxia, oxidative stress and relative vasospasm which in turn, determines increased coagulation and endothelial injury, damage of vascular endothelial cells, and finally periodontal tissue destruction [ 44 ]. Consequently, some evidence has been suggested that periodontal infection mediated by some pathogens such as A. actinomycetemcomitans may accelerate PT and endothelial damage and inflammatory response orchestrated through oxidative stress pathways [ 45 , 46 ], especially in obese patients [ 47 ]. In this respect, some evidence has shown that the tissue damage associated with PT was due to oxidative stress and, therefore, associated with high levels of nitric oxide (NO) and hs-CRP [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the effects of periodontitis on circulating ROS and oxidative stress. Studies have shown that dental pulp collected from teeth with periodontitis is inflamed under oxidative stress and presents increased levels of apoptosis and autophagy relative to normal dental pulp ( Li et al, 2019 ). The pathogenesis of periodontitis is related to an imbalance between ROS and the antioxidant defense system.…”
Section: Impact Of Pd On the Pathogenesis Of Ckdmentioning
confidence: 99%
“…We believe this gap was associated with the lacking of biological cues for cell. Inspired by the previous methods (Hu et al, 2017;Li et al, 2019;Wang et al, 2019), extracellular vesicles generated from cementum related cells were supposed to load inside the biomimetic cementum, which could significantly improve the cementogenic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The composition and hierarchical structure are the key issues endowing the cementum with unique biological and mechanical properties to fully exert its function. Unfortunately, the composition and hierarchical structure of cementum are extremely vulnerable under the frequentlyoccurring disease such as the root caries and periodontitis (Li et al, 2019). The destroyed cementum not only severely inhibits the bioactivity of PDL cells (PDLCs) and affects subsequent PDL formation, but also may initiate and aggravate root dentine resorption (Alyahya and Alqareer, 2017).…”
Section: Introductionmentioning
confidence: 99%